Mother's perspective of maintaining an active outdoor leisure time for a preschool child - Pišot, Saša (Annales kinesiologiae (Koper), 2020)
In the contemporary life of a family, mothers are often faced with a conflict between work and family in order to assure a healthy childhood for their children. How to pro-vide active leisure time for a child in accordance with healthy lifestyle guidelines, and what factors affecting the quantity and quality of a child%s physical activity, have been researched from the perspective of mothers. The qualitative and quantitative methods of questionnaires and semi-structured interviews (n=54) with mothers were executed with the aim to study important factors which distract mothers and their children from ensuring physically active leisure time. Additionally, the possible correlation of chil-dren%s motor efficiency and family characteristics were studied. From the mother%s per-spective we found that %lack of time% along with %weather conditions% were two major obstacles. Mothers also indicated %the access to recreational facilities% and %health of a child% as common impetuses for active outdoor leisure time. Additionally, compari-son of family characteristics showed that active family leisure behavior is influenced by i) demographic and personal factors of the family (family size, SES , sports history), ii) social factors (employment and schedule of employment, financial status of the family, social networks support), and iii) environmental factors (weather, accessibility, and safe conditions for physical activity, as well as living conditions). Because environmen-tal factors are harder to change, we need to pay attention to demographic, personal, and social factors of mothers (families) with reduced possibilities and enable them to ensure conditions for healthy child development.
Keywords: children; družine; families; gibalna aktivnost; gibanje; leisure time behavior; motor efficiency; motorična učinkovitost; okoljski dejavniki; osebni dejavniki; otroci; physical activities; predšolski otroci; prosti čas; socialni dejavniki; športna aktivnost